Flat epithelial atypia: conservative management of patients without residual microcalcifications post-vacuum-assisted breast biopsy - Schiaffino, Simone (Br J Radiol, 2018)
OBJECTIVE: To determine the malignancy rate (defined in this study as stability or absence of malignancy developed on close imaging follow-up post-biopsy) of conservative management in patients with a vacuum-assisted breast biopsy (VAB) diagnosis of flat epithelial atypia (FEA), performed on single group of microcalcifications, completely removed during procedure. METHODS: This is a retrospective, monocentric, observational study, approved by IRB. Inclusion criteria were: VAB performed on a single group of microcalcifications; the absence of residual calcifications post-VAB; diagnosis of isolated FEA as the most advanced proliferative lesion; radiological follow-up at least of 12 months. The personal history of breast cancer or other high-risk lesions was an exclusion criteria. The patients enrolled were conservatively managed, without surgical excision, through close follow-up: the first two mammographies performed with an interval of 6 months after biopsy, followed by annual mammographic and clinical checks. RESULTS: 48 consecutive patients were enrolled in the study, all females, with age range of 39–76 years (mean 53,3 years) and radiological follow-up range of 13–75 months (mean 41.5 months). All the lesions were classified as BI-RADS 4b. The diameter range of the group of calcifications was 3–10 mm (mean 5, 6 mm). In each patient, 7 to 15 samples (mean 11) were obtained. Among all the patients, there was only one case (2%) of new microcalcifications, developed in the same breast, 26 months after and 8 mm from the site of previous VAB, and interpreted as ADH at surgical excision. All the checks of the other patients were negative. CONCLUSION: Even with a limited follow-up, we found a malignancy rate lower than 2%, through a defined population. Further studies with bigger number of patients and extended follow-up are needed to reinforce this hypothesis. ADVANCES IN KNOWLEDGE: Surgical excision may not be necessary in patients with VAB diagnosis of isolated FEA, without residual microcalcifications post-procedure and considered concordant with the mammographic presentation, considering the low rate of malignancy at subsequent follow-ups.